2020
DOI: 10.1111/eje.12525
|View full text |Cite
|
Sign up to set email alerts
|

Teaching of dental implantology to undergraduate dental students: The Nigerian experience

Abstract: IntroductionDental implantology is an increasingly contemporary integral and important component of the practice of dentistry. This study assessed the level of teaching of dental implantology to dental undergraduates in Nigeria.Materials and MethodsThis was a cross‐sectional descriptive study involving the use of a self‐administered questionnaire consisting of five sections developed for this study. It was sent via e‐mail to a dental faculty in charge of and involved in the teaching of dental implantology in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Implantology must be taught to undergraduate students as it is the age of rehabilitation (n=10). 21 There is vast overlapping and repetition of course content in different subjects and subjects like General Medicine and General Surgery which should not be taught to that significant level. However, there is a contradiction with study from Harvard School of Dental Medicine which is in favor to break down the wall between Medicine and Dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…Implantology must be taught to undergraduate students as it is the age of rehabilitation (n=10). 21 There is vast overlapping and repetition of course content in different subjects and subjects like General Medicine and General Surgery which should not be taught to that significant level. However, there is a contradiction with study from Harvard School of Dental Medicine which is in favor to break down the wall between Medicine and Dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study that evaluated the practical knowledge of dentists reported similar findings. They noted that 71.8% of respondents reported the lack of practical experience as a significant barrier to practicing implant dentistry, [30] a fact that is given credence to by the largely theoretical based training, and little hands-on clinical experience undergraduate dental students are exposed to while in schoo.l [30,31] While theoretical knowledge provides the instructional foundation for a clinical implantology [32], the need to complement this with clinical experience cannot be over emphasized; a deficiency which manifests in an apathetic approach to implant-based therapy by dental practitioners.…”
Section: Clinical Knowledge and Expertisementioning
confidence: 99%
“…Currently in Nigeria, DI is now taught at undergraduate level in most of the dental schools 14 with various forms of pedagogical techniques employed to improve teaching 15 with additional plans to improve undergraduate teaching of dental implantology 14 . However, there is a dearth of information on the perception of dental implant providers themselves 16 with only a few studies reported in other countries 6,16,17 .…”
Section: Introductionmentioning
confidence: 99%